2-Carboxy-1-(3-nitrophenyl)ethanaminium perchlorate - Liang, Wen-Xian (International Union of Crystallography, 2010)
In the title compound, C(9)H(11)N(2)O(4) (+)·ClO(4) (−), the organic cations form centrosymmetric dimers via a pair of O—H⋯O hydrogen bonds between the carboxyl groups. In the crystal, N—H⋯O interactions between the protonated amine group and the perchlorate anions and the nitro group connect the components into a two-dimensional network parallel to (001).